Berpikir Kritis Dalam Filsafat Ilmu: Kajian Dalam Ontologi, Epistemologi dan Aksiologi - Semuel Unwakoly (Jurnal Filsafat Indonesia, 2022)
21st century learning emphasizes four aspects, one of which is critical thinking. From a philosophical perspective, critical thinking is a self-directed assessment that results in interpretation, analysis, evaluation, and inference, as well as an explanation of the evidence based on conceptual, methodological, criteriological, or contextual considerations on which thejudgment is based. Critical thinking has a long history, starting from the thought and teaching of Socrates and developing rapidly in the Middle Ages and the Renaissance era, with various theories and debates that continue to develop today. This article presents the ontological, epistemological, and axiological views of critical thinking through library research obtained from the analysis and synthesis of scientific articles in the field of science. The ontological view of critical thinking in science is focused on developing the ability to critically analyze discourse to develop action. In the view of epistemology, critical thinking is seen as a tool to increase understanding or as a tool to determine truth or untruth based on the views of scientists or academics. Meanwhile, in the axiological view of critical thinking, it can be seen from its usefulness in science. From the three views above, different areas of critical thinking in sciencecan be found.